Expressão do receptor do fator de crescimento epidérmico (EGFR) como fator prognóstico no colangiocarcinoma - Rodrigo Vieira Gomes (2016)
Cholangiocarcinoma is a malignant tumor originated in the epithelium of the bile ducts. Is the second commonest primary hepatic cancer. It shows poor prognosis and poor response to chemotherapy. Today, with the increase in incidence and the lack of effective treatment, there is an increased interest of research centers to identify factors that may influence the prognosis of patients and to find possible targets for cancer treatment. The expression of epidermal growth factor receptor (EGFR) in these tumors has proved as bad prognostic factor in some internationalstudies, but the results are still controversial. The aim of this study was to evaluate the expression of EGFR in patients with CCA, and its association with prognostic factors and survival. Clinical and laboratory data and surgical specimens, resection (n = 30) or biopsy (n = 11), of patients with CCA were analyzed. EGFR expression was assessed by immunohistochemistry. There was no significant difference in theproportion of men (n = 22) and women (n = 19). The average age of patients was 58 years, ranging from 28 to 83 years. There was a lower proportion of smokers, alcoholics and gallstones. Overexpression of EGFR has occurred in 28.6% of cases. The EGFR expression was not associated with anatomical classification nor the papillary architecture or non-papillary. Among 17 cases of papillary CCA, 5 (29.4%) were positive for EGFR and 12 (70.6%) were negative. The EGFR expression wasassociated with more advanced cases (stages III and IV) and lower patient survival (median 14.4 months in positive for EGFR and 41.8 months in the negative). Overall survival was 30.5 months and survival at 12, 24 and 36 months was 78.3%, 48.9% and 21.1%, respectively. Other factors that were associated with lower survival were intrahepatic location of tumors and low serum bilirubin levels (0-4 mg / dL). In conclusion, EGFR expression in cholangiocarcinoma was associated with worseprognosis, but will be necessary multicentric studies with larger number of cases to confirm this finding and to assess the real importance of this receptor as a therapeutic target.